ANTIBACTERIAL ACTIVITY AND KLT-BIOAUTOGRAPHY ANALYSYS OF ETHANOL EXTRACT OF KELOR LEAVES (Moringa oleifera L.) AGAINST Staphylococcus aureus dan Escherichia coli BACTERIES - Diena Elisa Cahyani; Bertha Rusdi; Lanny Mulqie (Bandung Conference Series: Pharmacy, 2023)
Abstract. Moringa leaves (Moringa oleifera L.) have a class of secondary metabolites that act as antibacterials. Research has been conducted on identifying secondary metabolite compounds with antibacterial activity in Moringa leaves using the KLT bioautography method. This study aims to determine the group of secondary metabolite compounds contained in the ethanol extract of moringa leaves that have the potential as antibacterials. The ethanol extract of moringa leaves was made by maceration method using ethanol solvent. Antibacterial testing in this study used the agar well method with 5%, 10%, 20%, 40%, and 80% b/v concentrations. The results showed that the KHM value of moringa leaf ethanol extract was 10% with inhibition zones on Staphylococcus aureus and Escherichia coli bacteria of 27.5 mm and 19.5 mm, respectively. Furthermore, the separation of secondary metabolites in the ethanol extract of moringa leaves was carried out using KLT with a stationary phase of silica gel GF254 and a mobile phase of chloroform: methanol (9: 1), then continued with a contact bioautography test. KLT bioautography results showed that the spot with an Rf value of 0.81 produced an inhibition zone. Identifying marks with corroborate, specific for flavonoid compounds, shows positive results, so it is concluded that secondary metabolite compounds with antibacterial activity are flavonoids. Abstrak. Daun kelor (Moringa oleifera L.) diduga memiliki golongan metabolit sekunder yang berperan sebagai antibakteri. Telah dilakukan penelitian mengenai identifikasi senyawa metabolit sekunder yang memiliki aktivitas antibakteri pada daun kelor dengan menggunakan metode KLT bioautografi. Penelitian ini bertujuan untuk mengetahui golongan senyawa metabolit sekunder yang terkandung pada ekstrak etanol daun kelor yang berpotensi sebagai antibakteri.Ekstrak etanol daun kelor dibuat dengan metode maserasi menggunakan pelarut etanol. Pengujian antibakteri pada penelitian ini menggunakan metode agar sumuran dengan konsentrasi 5%, 10%, 20%, 40%, dan 80% b/v. Hasilnya menunjukkan bahwa nilai KHM ekstrak etanol daun kelor adalah 10% dengan zona hambat pada bakteri Staphylococcus aureus dan bakteri Escherichia coli berturut-turut sebesar 27,5 mm dan 19,5 mm. Selanjutnya dilakukan pemisahan metabolit sekunder pada ekstrak etanol daun kelor menggunakan KLT dengan fase diam silika gel GF254 dan fase gerak kloroform:metanol (9:1) dilanjutkan dengan uji bioautografi kontak. Hasil KLT bioautografi menunjukan bahwa bercak dengan nilai rf 0,81 menghasilkan zona hambat. Identifikasi bercak dengan sitroborat yang spesifik untuk senyawa flavonoid menunjukan hasil positif, sehingga disimpulkan senyawa metabolit sekunder yang memiliki aktivitas antibakteri adalah flavonoid.